Social Theories of the Environment - Scarce, Rik (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This course really has two purposes. One is to expose you to an area of advanced sociological theory. Every subfield within the discipline attracts rigorous theorizing of the sort we will discuss, and some of the major perspectives represented in our readings—particularly Marxism, constructivism, and feminism—are among the dominant contemporary theories throughout sociology. Students who are interested in post-graduate study can benefit from a thorough examination of the theories underlying an area of study like environmental sociology because courses like this one will comprise the bulk of their graduate school classwork, even if they are not specifically interested in environmental sociology as an area of concentration.The other primary purpose of this course is to intensively explore social thought concerning the environment. A strong argument can be made—and people like former Vice President Al Gore have been making it for years—that no single subject is of more importance to all of humanity than our proper relationship with the ecosphere. If Gore and others are correct, we need the sort of foundation provided by social theory to adequately understand and address environmental problems. This course will expose you to the foremost of those theories.